Psychological First Aid Pada Anak-Anak Korban Bencana Di Dusun Tambak Rejo Semarang - menik tetha agustina; Puspita Puji Rahayu; Qurnia Fitriyatinur; Isti Mayasari (Literasi: Jurnal Pengabdian Masyarakat dan Inovasi, 2022)
PFA is psychological first aid, available at the community level provided by family, friends, volunteers for those who need support. PFA awarding has its own skills and wide reach. The assistance given to these children is used as a treatment for the traumatic feeling of the disaster that befell them. Theraplay is used as a therapy in dealing with the traumatic feelings felt by children in the face of disasters